2018
DOI: 10.1177/2058739218802442
|View full text |Cite
|
Sign up to set email alerts
|

Elevated uric acid levels in premenopausal female systemic lupus erythematosus patients: Association with potential or existing renal damage

Abstract: Do premenopausal female systemic lupus erythematosus (SLE) patients have a low incidence of hyperuricaemia (HU) as healthy premenopausal females? As of yet, there have been few studies. This study aims to investigate the serum uric acid (UA) levels of premenopausal female SLE patients and the associated clinical risk factors. 107 premenopausal female SLE patients were divided into two groups: the high UA SLE group (n = 45) and the normal UA SLE group (n = 62). In total, 50 age-matched healthy premenopausal fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Elevated uric acid has been linked to the development of new-onset renal damage in SLE [14It predominantly causes renal injury, which causes glomerular blood vessel hypertension, which eventually progresses to systemic hypertension [18]. Several studies have established hyperuricemia as a risk factor for renal damage and persistent injury.…”
Section: Country Results Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Elevated uric acid has been linked to the development of new-onset renal damage in SLE [14It predominantly causes renal injury, which causes glomerular blood vessel hypertension, which eventually progresses to systemic hypertension [18]. Several studies have established hyperuricemia as a risk factor for renal damage and persistent injury.…”
Section: Country Results Conclusionmentioning
confidence: 99%
“…Ryom Oh et al found a connection between uric acid and C3 levels, indicating that elevated uric acid activates the complement system, leading to C3 consumption via both classical and alternative pathways (P value <0.001) [13]. Furthermore, several studies have supported a significantly negative correlation between C3 and uric acid [16,18,23]. However, some studies reported no significant relationship between uric acid and C3 [4,5,17].…”
Section: Country Results Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial study showed that the incidence of hyperuricemia in premenopausal SLE patients was 42.06%, compared to an incidence of 14% in healthy young females. 11 Although hyperuricemia was closely related to kidney damage, it did not depend on renal failure, neither was it associated with the use of cyclosporin or azathioprine. These results suggested that premenopausal female SLE patients did not maintain normal levels of UA even though they were hyperestrogenic.…”
Section: Introductionmentioning
confidence: 99%